DARIUS: A Digital Twin to Improve the Performance of Quantum Key Distribution - Ahmadian, Morteza; Ruiz, Marc; Comellas, Jaume; Velasco, Luis (Journal of lightwave technology, 2024)
Polarization encoded Quantum Key Distribution (QKD) is attracting great attention as it generates unlimitedly and unconditionally secure keys for different use cases. Despite its theoretical excellence based on quantum physics, commercial optical devices supporting QKD systems lack precision, which highly limits the final Key Exchange Rate (KER) of the system. Beside optical component imperfections, eavesdropping and unpredicted environmental events occurred in the quantum channel increase quantum Bit Error Rate (qBER), which leads to further KER reduction. In this article, we propose DARIUS, a digital twin for polarization encoded QKD systems that bridges the gap between perfect theoretical QKD systems and real implementations to: i ) address optical components' non-ideal behavior; ii ) discern eavesdropping from high qBER; and iii ) dynamically compensate for environmental events. Taking advantage of DARIUS, even moderate eavesdropping rates can be distinguished from qBER. Moreover, significant improvement in proactive environmental event compensation is achieved, as DARIUS can derive proper optical component tuning.